The in vitro response of phenotypically defined mouse stem cells and myeloerythroid progenitors to single or multiple growth factors. - Heimfeld, S (1991)
Pluripotential stem cells (Thylo Lin- Sca+; referred to as Sca+) and primitive myeloerythroid progenitor cells (Thylo Lin- Sca-; referred to as Sca-), defined by their in vivo repopulating properties, have been purified from mouse bone marrow. In this study, the growth factor requirements of these two subsets were compared in colony-forming assays. Sca- progenitor cells grew well in interleukin (IL) 3 alone and showed maximum growth when two factors, IL-3 plus IL-1 or IL-3 plus IL-6, were combined. In contrast, Sca+ stem cells were generally not responsive to any single factor tested. Some colony formation was found when IL-3 was paired with either IL-1 or IL-6, and this was significantly enhanced as additional factors were included. A remarkable frequency of as much as 1 colony per 1.7 input Sca+ cells was achieved when IL-1, IL-3, IL-6, and colony-stimulating factors were used together. These differences in factor requirements presumably reflect the need for multiple factor signaling in the more primitive stem cell population. In most other aspects of colony formation, Sca+ and Sca- cells were very similar. They generated colonies that had equivalent distributions in size and cellular composition. One notable difference was found in the kinetics of their response. Whereas nearly all Sca- cells formed colonies within 7 days, a significant fraction of Sca+ cells delayed colony formation for greater than 1 week. During this quiescent period, cell survival was absolutely dependent on the presence of factors in the medium.